Pengaruh Sistem Pengendalian Internal terhadap Intensitas Inovasi dan Kinerja Organisasi Sektor Publik di Surabaya dengan Kepemimpinan Transformasional sebagai Variabel Moderasi - Putri Farnisa Wahida; Diah Hari Suryaningrum (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study examines the relationship between the ICS and the performance of public sector organizations in Surabaya, with the mediation model of innovation intensity and the moderation model of transformational leadership. The population of this research is public sector organizations in Indonesia, which are 17.307 organizations. The sampling selected using a purposive sampling method. This type of research is quantitative with primary data obtained from research questionnaires. The analytical method used is SEM-PLS with Smart PLS 4. The results show that the ICS has a direct effect on the performance of public sector organizations, but has no effect when the innovation intensity mediation model is added, the intensity of innovation does not affect the performance of public sector organizations, and moderating of transformational leadership model does not affect the relationship between ICS and performance of public sector organizations, ICS and innovation intensity, innovation intensity and performance of public sector organizations. The results of this study emphasize the importance of implementing an ICS in public sector organizations and the role of policymakers in encouraging the implementation process. Keywords: Internal Control System, Performance of Public Sector Organization, Innovation Intensity, Transformational Leadership